Arginine methylation augments Sbp1 function in translation repression and decapping - Bhatter, Nupur; Roy, Raju; Shah, Shanaya; Sastry, Sneha P; Parbin, Sabnam; Iyappan, Rajan; Kankaria, Siddharth; Rajyaguru, Purusharth I (The FEBS journal, 2019)
The fate of messenger RNA in cytoplasm plays a crucial role in various cellular processes. However, the mechanisms that decide whether mRNA will be translated, degraded or stored remain unclear. Single stranded nucleic acid binding protein (Sbp1), an Arginine-Glycine-Glycine (RGG-motif) protein, is known to promote transition of mRNA into a repressed state by binding eukaryotic translation initiation factor 4G1 (eIF4G1) and to promote mRNA decapping, perhaps by modulation of Dcp1/2 activity. Sbp1 is known to be methylated on arginine residues in RGG-motif; however, the functional relevance of this modification in vivo remains unknown. Here, we report that Sbp1 is arginine-methylated in an hnRNP methyl transferase (Hmt1)-dependent manner and that methylation is enhanced upon glucose deprivation. Characterization of an arginine-methylation-defective (AMD) mutant provided evidence that methylation affects Sbp1 function in vivo. The AMD mutant is compromised in causing growth defect upon overexpression, and the mutant is defective in both localizing to and inducing granule formation. Importantly, the Sbp1-eIF4G1 interaction is compromised both for the AMD mutant and in the absence of Hmt1. Upon overexpression, wild-type Sbp1 increases localization of another RGG motif containing protein, Scd6 (suppressor of clathrin deficiency) to granules; however, this property of Sbp1 is compromised in the AMD mutant and in the absence of Hmt1, indicating that Sbp1 repression activity could involve other RGG-motif translation repressors. Additionally, the AMD mutant fails to increase localization of the decapping activator DEAD box helicase homolog to foci and fails to rescue the decapping defect of a dcp1-2Δski8 strain, highlighting the role of Sbp1 methylation in decapping. Taken together, these results suggest that arginine methylation modulates Sbp1 role in mRNA fate determination.
Keywords: Methylation; Arginine; Amino Acid Motifs; RNA, Messenger; messenger RNA; Selenium-Binding Proteins; posttranslační úpravy proteinů; Amino Acid Sequence; western blotting; cirkulární dichroismus; aminokyselinové motivy; Circular Dichroism; sekvence aminokyselin; Saccharomyces cerevisiae Proteins; Blotting, Western; Saccharomyces cerevisiae - proteiny; arginin; Protein Processing, Post-Translational; cytoplazmatická granula; proteiny vázající selen; Protein Binding; metylace; Cytoplasmic Granules; vazba proteinů